The Effect of Coconut Water in Reducing Fatigue among Workers in North Sumatera - Rajagukguk, Bona Rina Ria; Nurmaini, Nurmaini; Sudaryati, Etti (Indonesian Journal of Medicine, 2018)
Background: Fatigue can reduce working performance, worker motivation, and work productivity. Fatigue due to exposure to heat pressure which causes excessive sweating must be overcome through the provision of fluids that are right for workers. Coconut water contains electrolytes, so it is very good to replace lost body fluids during activities throughout the day. The purpose of this study is to analyze differences in work fatigue with interventions giving 4 liters of drinking water and giving 1 liter of young coconut water (Cocos nucifera L.) accompanied by giving 3 liters of drinking water.Subjects and Method: This study is a quasi-experimental design with a research design of one group pre and post-test design. The study population was the production of cassava chips factory workers with a total sample of 20 people. The sampling technique is purposive sampling. The dependent variable is work fatigue while the independent variable is giving 4 liters of drinking water and giving 1 liter of young coconut water (Cocosnucifera L) accompanied by giving 3 liters of drinking water. The type of data collected is primary data in the form of work fatigue (in milliseconds) measured using the Reaction Timer. Bivariate analysis was conducted using the paired T-test.Results: Fatigue after giving 1 liter of young coconut water and 3 liters of drinking water was lower (mean = 118.00; p = 0.001) than the group given 4 liters of drinking water (mean 164.94; p= 0.001).Conclusion: Work fatigue in the group given 1 liter of young coconut water and 3 liters of drinking water was lower than the group given 4 liters of drinking water.Keywords: fatigue, young coconut water, drinking water, heat pressureCorrespondence: Bona Rina Ria Rajagukguk. Department of Occupational Health and Safety, Faculty of Public Health, Universitas Sumatera Utara, Medan, North Sumatera. Email: bonarinaria@gmail.com. Mobile: 081370185933.Indonesian Journal of Medicine (2018), 3(3): 173-179https://doi.org/10.26911/theijmed.2018.03.03.08